Phase diagrams of kappa/iota-hybrid carrageenans : the role of chemical structure and type of salt - Azevedo, Gabriela (2013)
Kappa/iota-hybrid carrageenans (KI) are food additive which recently attracted an increased scientific and industrial interest as these are valuable sustainable alternative to kappa- and iota-carrageenans. Optimized KI (in terms of gel properties) have been isolated from Mastocarpus stellatus [1], Chondrus crispus and Anhfeltiopsis devenionsis seaweeds, thus providing a palette of chemical structures and inherent gel elasticity. Here we report the phase diagrams of these KI in the presence of KCl or NaCl salts. KI hot solutions prepared at different polysaccharide concentrations and ionic strengths were stored at room temperature (230C) for 24h. The systems were then sorted visually in gels, solutions and biphasic gel + solution phases. The biphasic systems were further classified in gels exhibiting syneresis (where the liquid phase is essentially a salt solution expelled from the gel) and in suspensions (gelled particles suspended in salt solution). Solutions and suspensions were submitted to steady shear rate sweeps in order to assess their respective flow curves, whereas gels were studied with penetration tests to evaluate their Young modulus (E), non linear behavior and strain at break. We report for the first time the effect of KI chemical structure on the phase diagrams and provide a systematic comparison with equivalent mixture of kappa- and iota-carrageenans. References [1] Azevedo, G., Hilliou, L., Bernardo, G., Sousa Pinto, I., Adams, R. W., Nilsson, M., Villanueva, R. D. 2013. Tailoring kappa/iota-hybrid carrageenan from Mastocarpus stellatus with desired gel quality through pre-extraction alkali treatment. Food Hydrocolloid. 31, 94-102.